OTAK RASIONAL DAN OTAK INTUITIF DALAM PENDIDIKAN ISLAM - Sidik Purnomo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The rational brain has indeed been widely reviewed by researchers, but the existence of an intuitive brain has not been widely known to date. This article aims to explain the rational and intuitive brains in Islamic education. This study is a literature review with a descriptive qualitative approach. Techniques of data analysis using clarification, comparison and interpretation of the themes of neuroscience, rational brain, an intuitive brain that I associate with Islamic Education. From the reality that exists in the world of education we often encounter a lack of serious students in learning Islamic Education which consequently the ability of students' knowledge in Islamic Education is very low, with educators need to know rational and intuitive brain functions that exist in each student so the effort to improve the quality of Islamic Education. The results of this study indicate that there is a close connection between thinking using a rational and intuitive brain that is when the rational brain is maximized and reaches fatigue, then intuitively will work and find unexpected answers